Melatonin Protects Against Neuronal Apoptosis via Suppression of the ATF6/CHOP Pathway in a Rat Model of Intracerebral Hemorrhage - Xu, Weilin; Lu, Xiaoyang; Zheng, Jingwei; Li, Tao; Gao, Liansheng; Lenahan, Cameron; Shao, Anwen; Zhang, Jianmin; Yu, Jun (Frontiers in Neuroscience, 2018)
Neuronal apoptosis plays a key role in secondary brain injury caused by intracerebral hemorrhage (ICH). This study first showed that inhibition of activating transcription factor 6 (ATF6) could alleviate secondary brain injury through anti-apoptosis after ICH in rats. The melatonin, ATF6 and CCAAT/enhancer-binding protein homologous protein (CHOP) siRNAs were applied in this study. Brain water content, behavioral assessment, blood-brain barrier (BBB) leakage were evaluated at 24h after ICH. Western blot analysis was used to evaluate the protein level of target proteins (ATF6, CHOP, Bip, Bcl-2, Bax, and cleaved caspase-3). Reverse transcription-polymerase chain reaction (RT-PCR) was used to assess the mRNA level of ATF6, CHOP and cleaved caspase-3. Terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) and caspase-3 immunofluorescence staining were applied to evaluate the neuronal cell death. The results suggested that the levels of ATF6 and its downstream protein, CHOP, were upregulated and reached the peak at 24h after ICH. ATF6 was highly expressed in neurons. The administration of melatonin significantly decreased the mRNA and protein levels of ATF6, and its downstream targets, CHOP and cleaved caspase-3, but increased the Bcl-2/Bax ratio, which ameliorated the neurological functions. The CHOP siRNA significantly reversed the pro-apoptotic effect induced by the increased ATF6 level after ICH. Melatonin could protect against neuronal apoptosis via suppression of ATF6/CHOP arm of ER-stress-response pathway.